COLLABORATIVE GOVERNANCE MODEL IN INDONESIAN INNOVATION STARTUP PROGRAM: THE MASKIT STARTUP CASE STUDY - Asropi Asropi; Annisa Daniati; Maria Ulfa (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to identify, describe, and analyze collaborative governance models of public services in the Indonesian Innovation Startup (SII) program conducted by the Directorate of Technology-Based Start-ups, National Research and Innovation Agency (BRIN). This study uses the Integrative Framework for Collaborative Governance in realizing organizational goals. This concept is used in order to analyze the role of stakeholders in participating in realizing collaborative government governance in the implementation of the Indonesian Innovation Startup program. This research uses qualitative research with the case study method of the Maskit startup in the Indonesian Innovation Startup (SII) program. The data sources come from documents regarding the SII program and the concept of collaborative governance as well as interviews from various sources. The data are collected through interviews, observations, and documentation carried out by involving related parties, namely the program organizers (government), participants (startup companies), and incubators. The results of the study show that the collaborative governance process in the SII program followed by the Maskit startup, has generally implemented the concept of the Integrative Framework for Collaborative Governance. All elements within the framework, including principled engagement, shared motivation, and joint capacity, have been implemented by all stakeholders involved, namely BRIN as the organizer of the SII program, Maskit as the startup participating in SII, and University of Indonesia as the incubator. This research is expected to enrich academic studies on collaborative governance in the realm of public policy and can be used as a reference for those who wish to conduct similar research or create collaborative programs with elements of government, universities, SMEs, and various other relevant parties.